In vitro Antioxidant and Antiproliferative Activities of Various Solvent Fractions from Clerodendrum viscosum Leaves - Shendge, Anil Khushalrao (Pharmacogn Mag, 2017)
BACKGROUND: Free radicals such as reactive oxygen and nitrogen species, generated in the body, play an important role in the fulfillment of various physiological functions but their imbalance in the body lead to cellular injury and various clinical disorders such as cancer, neurodegenaration, and inflammation. OBJECTIVE: The objective of this study is to fight this problem, natural antioxidant from plants can be considered as possible protective agents against various diseases such as cancer which might also modify the redox microenvironment to reduce the genetic instability. This study was designed to evaluate the antioxidant and antiproliferative potential of Clerodendrum viscosum fractions against various carcinomas. MATERIALS AND METHODS: In this present study, 70% methanolic extract of C. viscosum leaves have been fractionated to obtain hexane, chloroform, ethyl acetate, butanol, and water fractions, which were tested for their antioxidant and anticancer properties. RESULTS: It was observed that chloroform and ethyl acetate fractions showed good free radical scavenging properties as well as inhibited the proliferation of human lung cancer (A459), breast (MCF-7), and brain (U87) cells. Moreover, they arrested the cell cycle at G2/M phase of breast and brain cancer. These inhibitory effects were further confirmed by bromodeoxyuridine uptake imaging. Phytochemical investigations further indicate the presence of tannic acid, quercetin, ellagic caid, gallic acid, reserpine, and methyl gallate which might be the reason for these fractions’ antioxidant and antiproliferative activities. CONCLUSION: Clerodendrum viscosum leaf chloroform and Clerodendrum viscosum leaf ethyl acetate fractions from C. viscosum showed good reactive oxygen species and reactive nitrogen species scavenging potential. Both the fractions arrested cell cycle at G2/M phase in MCF-7 and U87 cells which lead to induce apoptosis. SUMMARY: Crude extract of Clerodendrum viscosum leaves was fractionated using different solvents. Among them, chloroform and ethyl acetate fractions exhibited excellent free radical scavenging properties. The same fractions inhibited the proliferation of human lung cancer (A459), breast (MCF-7), and brain (U87) cells. Chloroform and ethyl acetate fractions arrested the cell cycle at G2/M phase of breast and brain cancer. Phytochemical investigations further indicate the presence of several bioactive principles present in them. Abbreviations used: CVLME: Clerodendrum viscosum leaf methanolic extract; CVLH: Clerodendrum viscosum leaf hexane; CVLC: Clerodendrum viscosum leaf chloroform; CVLE: Clerodendrum viscosum leaf ethyl acetate; CVLB: Clerodendrum viscosum leaf butanol; CVLW: Clerodendrum viscosum leaf water; BrdU: Bromodeoxyuridine; WST-1: Water soluble tetrazolium salt.